2021
DOI: 10.1097/mao.0000000000003393
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Postural Sway in Patients With Persistent Postural-Perceptual Dizziness (PPPD) Using Wearable Motion Sensors

Abstract: Objective: To extend previous investigations of postural control in patients with persistent-postural perceptual dizziness (PPPD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
2
15
1
Order By: Relevance
“…and demographic characteristics, such as a relatively young distribution with anxious/depressive background observed in the present PPPD group, were consistent with those in previous studies (Kim et al, 2020;Bittar and von Sohsten Lins, 2015). The results of posturography in this study were consistent with those in previous reports (Sohsten et al, 2016;McCaslin et al, 2022), showing significant differences in the eyes-closed condition but not in the eyes-open condition compared with HCs.…”
Section: Clinical and Demographic Characteristics Of Persistent Postu...supporting
confidence: 93%
“…and demographic characteristics, such as a relatively young distribution with anxious/depressive background observed in the present PPPD group, were consistent with those in previous studies (Kim et al, 2020;Bittar and von Sohsten Lins, 2015). The results of posturography in this study were consistent with those in previous reports (Sohsten et al, 2016;McCaslin et al, 2022), showing significant differences in the eyes-closed condition but not in the eyes-open condition compared with HCs.…”
Section: Clinical and Demographic Characteristics Of Persistent Postu...supporting
confidence: 93%
“…PPPD brings together varying aetiological and mechanistic models, and evolves from previously described visual vertigo, space-motion discomfort, phobic postural vertigo and chronic subjective dizziness, the latter which removed the need for specific psychological factors to be present. Its pathophysiology is thought to include locomotion and spatial orientation alterations (eg, abnormal postural control stiffening3 and visual dependence4), appropriate adaptations during mobility threats (eg, acute vestibular illnesses), but maladaptive when maintained after acute illness remission. Current pathophysiological models5 hypothesise that these brain functioning shifts are linked to predisposing factors that may be identifiable early in the illness, perhaps before PPPD’s onset, making them possible PPPD predictors.…”
Section: Introductionmentioning
confidence: 99%
“…standing on foam), compared to controls. [19][20][21] Automated postural and gait parameters in other studies have shown promise as potential diagnostic biomarkers to differentiate patients with peripheral vestibular, cerebellar and persistent postural-perceptual dizziness, 19,22,23 but these instruments are not routinely available. A stiffened ankle strategy with a high frequency of body sway (3.5-8 Hz) has been reported in patients with phobic postural vertigo (a precursor term to persistent posturalperceptual dizziness), related to a tendency to abnormally recruit afferent feedback loops during a quiet stance.…”
Section: Making a Diagnosismentioning
confidence: 99%